Investigation of Catalytic Oxidation and Coupling Reactions on Gold, Palladium, and Gold-palladium Alloys - (:unkn) unknown (My University, 2017)
Polyvinyl acetate is a common adhesive and additive to emulsion-based paints produced in the millions of tons per year through the palladium catalyzed coupling of ethylene and acetic acid. Understanding the reaction mechanism and kinetics is integral to designing a more efficient catalyst through an increase in activity, selectivity, or both. It has been shown that selectivity for the vinyl acetate monomer (VAM) reaction increases to ~94% upon alloying palladium with gold compared to palladium alone (~80% selective). The characterization of the VAM formation reaction on Pd(111) and Au/Pd(111) single crystal alloys has been extensively studied, but it has been shown that Pd(100) and particularly Au/Pd(100) alloys have an increased activity to Pd(111) and Au/Pd(111) catalysts. Competing reaction mechanisms have also been proposed for Pd(100) catalysts for the coupling of ethylene and acetic acid. To investigate the increased reaction rate on these surfaces and to elucidate the reaction pathway the behavior of the reactants, a detailed reaction mechanism, and the kinetics of the VAM formation reaction on Pd(100) and Au/Pd(100) alloys are presented here. Another relevant catalytic process is the oxidation of carbon monoxide on gold (typically studied on supported gold nanoparticles). This reaction is of interest as CO is a common catalyst poison that binds strongly to many reactive transition metal catalysts. It is shown that by using ozone as an atomic oxygen source, CO oxidation occurs even on Au(111) single crystals. Two CO adsorption sites are observed after ozone exposure with CO oxidation occurring at as low as ~140 K. The Au/Pd(100) alloy catalysts were also studied for their hydrogen adsorption behavior in an attempt to reconcile differences in previous work on hydrogen adsorption on Au/Pd alloys. Hydrogen is found to adsorb in two subsurface states as well as surface chemisorbed states, that, when further exposed to CO, become trapped in the subsurface of the alloy to elevated temperatures because of CO adsorption/blocking of palladium surface sites. Upon CO desorption, hydrogen desorption occurs through now-vacant palladium surface sites.
Keywords: Catalysis; Single Crystal; Surface Chemistry